Current epidemiological status of mosquito-borne arboviruses in Gulf countries: a systematic review and meta-analysis - Khalid Hajissa; Mutiat Hammed-Akanmu; Hussain Omar Alfaqih; Ahmad A. Alshehri; Mohammed Dauda Goni; Maha Al-Asmakh (Tropical Diseases, Travel Medicine and Vaccines)
Abstract Background Mosquito-borne viral (MBV) infections caused by dengue virus (DENV), Rift Valley fever virus (RVFV), West Nile virus (WNV), and chikungunya virus (CHIKV) pose a significant global public health concern. The aim of this systematic review is to summarise the reported prevalence data for these viruses in Gulf countries. Methods A web search in four electronic databases (Scopus, PubMed, Google Scholar, and Web of Science) was conducted, and forty-four eligible studies were fulfilled the selection criteria and were therefore included in this study. The Pooled prevalence of MBVs was estimated using a random-effects model. The heterogeneity was assessed using Cochrane Q test and I 2 test, while publication bias was evaluated using Egger’s test. Results Using meta-analysis of proportions, the pooled prevalence of MBVs in Gulf countries among 34,367 human and 19,062 Animal samples was estimated to be 22.5% (95% CI: 13.7–31.4) and 11.6% (95% CI: 0.5 − 22.7%), respectively. In human, DENV was the most predominant virus reported in 19 studies, with an overall pooled prevalence of 32.4%, followed by RVFV in 9 studies, with an infection rate of 10.1%, while WNV and CHIKV were only reported in two studies, with overall prevalence rates of 6.4% and 2.4%, respectively. On the other hand, the overall prevalence of WNV and RVFV in animals was estimated to be 27.7% and 1.5%, respectively. Conclusion This review revealed that MBVs are highly prevalent among humans in Gulf countries but relatively low in animals. As a result, additional therapeutic and preventive measures are required. However, the study highlights the need for further studies and surveillance to precisely monitor the burden of these viruses in the region.